Decreased Peripheral Blood ALKBH5 Correlates with Markers of Autoimmune Response in Systemic Lupus Erythematosus. (25th June 2020) - Luo, Qing; Fu, Biqi; Zhang, Lu; Guo, Yang; Huang, Zikun; Li, Junming
Abstract : Although it has been proved that the epigenetic modification of DNA and histones is involved in the pathogenesis of systemic lupus erythematosus (SLE), there is no study to explore whether the modification of N6-methyladenosine (m6A) in RNA is involved. In this study, the mRNA levels of m6A "writers" ( METTL3, MTEEL14, and WTAP ), "erasers" ( FTO and ALKBH5 ), and "readers" ( YTHDF2 ) in peripheral blood were determined by quantitative reverse transcription-polymerase chain reaction (qRT-PCR). The results demonstrated that the mRNA levels of METTL3, WTAP, FTO, ALKBH5, and YTHDF2 in peripheral blood from SLE patients were significantly decreased. The levels of ALKBH5 mRNA in SLE patients were associated with anti-dsDNA, antinucleosome, rash, and ulceration. Multivariate logistic regression analysis showed that the level of ALKBH5 mRNA in peripheral blood is a risk factor of SLE (P < 0.001 ). Moreover, our results suggested that there was a positive correlation between m6A"writers" ( METTL3 and WTAP ), "erasers" ( FTO and ALKBH5 ), and "readers" ( YTHDF2 ) in SLE patients. This study suggests that the mRNA level of ALKBH5 in peripheral blood may be involved in the pathogenesis of SLE.